Relationships between stakeholder orientation, corporate social responsibility and performance of small and medium enterprises in the tourism sector / Hanis Afifah Hamdan Azhar - Hamdan Azhar, Hanis Afifah (2023)
The COVID-19 pandemic has unmasked unprecedented impact on numerous business sectors and the tourism sector in Malaysia has not been spared. The tourism industry in Malaysia has been struck the hardest by the drop in tourist numbers as the country closed its borders to tourists. Without tourists’ arrival, SMEs performance is likely to be affected and, on this premise, this study seeks to understand the relationship between stakeholder orientation in the tourism industry, corporate social responsibility (CSR) and the performance of Small Medium Enterprises (SMEs) involved in this sector. Freeman theory of stakeholder orientation consisting of market orientation (customer and competitor), employee orientation and supplier orientation was the basis for the research framework and the interaction between stakeholders’ orientation and SMEs’ performance was postulated to be mediated by corporate social responsibility (CSR). This study employed quantitative method of simple random sampling (probability sampling). A total of 180 small and medium-sized companies involved in the tourism sector were the final through the survey method using a structured questionnaire as the instrument, the study was conducted using E-mail and the results were analysed using Partial Least Squares (PLS) and SPSS statistical tool.